2018
DOI: 10.36108/ljerhrm/8102.01.0112
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Style and Employee Performance in Nigerian Oil and Gas Sector

Abstract: This study examined the relationship between transactional and transformational leadership styles and employee performance in the Nigerian oil and gas sector using Lubcon Oil and Orientry Ltd as study area. Survey design was adopted:, a sample size of 100 was used representing the total population of the study, convenient sampling used to select the study firms while stratified sampling was used to samples from all departments in the firms. Copies of questionnaire were administered to members of staff of Lubco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…The results of this study indicate that Leadership Style has a significant effect on employee performance so it can be concluded that the role of the leader is one of the main factors that can improve employee performance, so the leader must plan the right strategy in running the organization, reviewing the performance of each individual, so that the leader knows what to do can make employee performance optimal. Some studies support that leadership style has an effect on employee performance such Olabode, Bakare, and Iheonunekwu (2020); Nawoselng'ollan and Roussel (2017).…”
Section: Leadership Style and Employee Performancementioning
confidence: 99%
“…The results of this study indicate that Leadership Style has a significant effect on employee performance so it can be concluded that the role of the leader is one of the main factors that can improve employee performance, so the leader must plan the right strategy in running the organization, reviewing the performance of each individual, so that the leader knows what to do can make employee performance optimal. Some studies support that leadership style has an effect on employee performance such Olabode, Bakare, and Iheonunekwu (2020); Nawoselng'ollan and Roussel (2017).…”
Section: Leadership Style and Employee Performancementioning
confidence: 99%